2019
DOI: 10.1111/een.12751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing and exposure of sunflower pollen on a common gut pathogen of bumble bees

Abstract: 1. Several bee species are declining due to multiple factors, including pathogens. Ingestion of sunflower (Helianthus annuus) pollen can dramatically reduce the bumble bee gut pathogen Crithidia bombi, but little is known about how timing and exposure to sunflower pollen consumption affects pathogen load.2. Two experiments were carried out to investigate how exposure to sunflower pollen relative to pathogen exposure affects Crithidia bombi in Bombus impatiens. Foraging trials with pollen-producing and male-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…We isolated major secondary compounds of sunflower and tested their efficacy against a common bumble bee gut pathogen; we also assessed the effects of numerous fatty acids from sunflower pollen, singly and in combination. Although we found that sunflower pollen consistently reduced Crithidia compared to control pollens, matching previous work (Giacomini et al 2018;LoCascio et al 2019a;LoCascio et al 2019b), none of the compounds we tested appear to be the sole mechanism driving this result, as none of them significantly reduced pathogen counts relative to control pollens. Although we did not test protein content in this study, it seems unlikely that protein content is the underlying mechanism since protein concentrations are similarly low in buckwheat and sunflower pollen (Yang et al 2013) but outcomes of these diets for Crithidia infection are very different.…”
Section: Discussionsupporting
confidence: 89%
“…We isolated major secondary compounds of sunflower and tested their efficacy against a common bumble bee gut pathogen; we also assessed the effects of numerous fatty acids from sunflower pollen, singly and in combination. Although we found that sunflower pollen consistently reduced Crithidia compared to control pollens, matching previous work (Giacomini et al 2018;LoCascio et al 2019a;LoCascio et al 2019b), none of the compounds we tested appear to be the sole mechanism driving this result, as none of them significantly reduced pathogen counts relative to control pollens. Although we did not test protein content in this study, it seems unlikely that protein content is the underlying mechanism since protein concentrations are similarly low in buckwheat and sunflower pollen (Yang et al 2013) but outcomes of these diets for Crithidia infection are very different.…”
Section: Discussionsupporting
confidence: 89%
“…Some native plants can be planted in agricultural land dominated by corn and soybean to increase forage diversity in early season. For example, sunflower ( Helianthus annuus L. [Asterales: Asteraceae]) can have medication effect on bees, and could be an option for forage enhancement ( Jonathan et al 2018 , LoCascio et al 2019 ). Efforts to conserve beneficial insects have revealed that native plants commonly found in prairies, the dominant habitat in Iowa before European settlement, are highly attractive to native pollinators as well as managed honey bees ( Tuell et al 2008 , Blaauw and Isaacs 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The timing and duration of exposure to antiparasitic floral products can strongly influence the strength of their inhibitory effects, as we have already seen with the example of callunene in heather nectar ( Koch et al, 2019 ). In another example, while the consumption of sunflower pollen over the span of one week dramatically reduced C. bombi infection in B. impatiens workers, sunflower pollen consumption limited to a 3.5 day period had less inhibitory effect, particularly if consumption was delayed for several days after initial infection ( LoCascio et al, 2019b ). Moreover, one-time consumption of sunflower pollen at the time of infection had no effect on ultimate infection intensity ( LoCascio et al, 2019b ).…”
Section: The Influence Of Antiparasitic Effects Of Floral Products On...mentioning
confidence: 99%